INVESTIGATING THE CAPABILITIES OF ADAPTIVE LEARNING AS A CUTTING-EDGE APPROACH TO MODEL DEVELOPMENT IN AN EDUCATIONAL SETTING - Marzuki, Marzuki; Zakaria, Nanang; Masruri, Masruri (PT Altin Riset Publishing, 2024)
Adaptive learning has become a significant topic in the development of modern education due to its potential to enhance the effectiveness and inclusivity of learning. This research aims to explore the potential of adaptive learning as an innovative model of development in the context of education. To gain a comprehensive understanding of the implementation of adaptive learning, the research methodology employs observation, interviews, and data analysis. The findings indicate that there is a perception gap among teachers, students, and parents regarding adaptive learning, as well as technical and practical challenges in its implementation. Furthermore, psychological aspects of students, such as learning motivation, also need to be considered in designing effective adaptive learning models. Thus, this research concludes that adaptive learning holds great potential for improving the effectiveness and inclusivity of education, but it requires appropriate support and strategies in its implementation.